International overhead cost sharing - Helmut Zink (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1997)
In this paper I investigate the effect of different stages of international trade on market structure and prices when production involves overhead cost, markets are intransparent, and customers have to search for offers. I show that two stages have to be distinguished: a first stage where each firm can offer its product in any country but customers cannot search in foreign countries and a second stage where each firm can offer in any country and each customer can search and buy in any country. In particular I investigate who benefits if one country increases its degree of market transparency and who benefits if the second stage of international trade is introduced.
Keywords: 330; Versicherungsmarkt; Unvollkommene Information; Außenwirtschaftstheorie; Skalenertrag; Preistheorie; Theorie